Development of styrene-acrylic polymeric compositions for the coating of textile materials used for packing - Saribyekova, Yulia; Kunik, Aleksandra; Asaulyuk, Tatyana; Semeshko, Olga; Myasnykov, Sergey (Eastern-European Journal of Enterprise Technologies, 2017)
As a result of the determination of the chemical, physical-chemical and physical and mechanical properties of individual styrene-acrylic polymers and their compositions with crosslinking agents, it has been found that the formation of a strong three-dimensional spatial structure of films provides the styrene-acrylic polymer Lacrytex 430. It is possible to use this polymer without crosslinking agents. The additional introduction of Laproxide and Appretta ECO into the composition lowers the degree of structuring of polymer films. It was established that for the Lacrytex 640 preparation, which has a low structuring index, the introduction of the glycidyl ester of the Laproxide 703 trade mark leads to an increase in the degree of crosslinking to 7.9 % and, as a result, to an increase in the resistance to organic solvents, to a reduction of hydrolytic degradation at high temperatures and to an increase in the physical-mechanical indicators. Taking into account the need to obtain low-content compositions that provide a complex of necessary properties to the final product, the use of individual styrene-acrylic polymer Lacrytex 430 and Lacrytex 640/Laproxide 703 composition, which provides obtaining elastic coatings, is actual and economically sound.